2006
DOI: 10.1007/s00520-005-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Brief oral cryotherapy for the prevention of high-dose melphalan-induced stomatitis in allogeneic hematopoietic stem cell transplant recipients

Abstract: We previously reported the efficacy of oral cryotherapy for the prevention of high-dose melphalan-induced stomatitis. The purpose of this study was to evaluate whether the further shortening of the duration of oral cryotherapy could minimize its side effects while sparing its efficacy. Seventeen consecutive recipients of allogeneic hematopoieic stem cell transplant conditioned with high-dose melphalan in combination with fludarabine alone or with fludarabine and additional radiation were enrolled in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 11 publications
0
26
0
2
Order By: Relevance
“…The administration of lenograstim at a dose of 5 mg/kg was initiated 1 day after HSCT and continued until neutrophil recovery was achieved. After April 2003, oral cryotherapy was applied for the prophylaxis of oral mucositis due to high-dose melphalan as we previously described [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…The administration of lenograstim at a dose of 5 mg/kg was initiated 1 day after HSCT and continued until neutrophil recovery was achieved. After April 2003, oral cryotherapy was applied for the prophylaxis of oral mucositis due to high-dose melphalan as we previously described [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…15, 16, 33-38 To address the optimal duration of cryotherapy in patients receiving melphalan, a study found that a total duration of cryotherapy for 60 minutes compared with 120 minutes improved tolerability without decreasing efficacy. 36 Other studies in patients undergoing HSCT have shown that oral cryotherapy also reduces opioid use 37 and decreases the need for parenteral nutrition. 38 …”
Section: Oral Mucositismentioning
confidence: 99%
“…Before BMT, patients are treated with myeloablative therapy, which reduces the renewal rate of the basal epithelium resulting in localised or diffuse ulceration of the mucosa and inflammation [2,8,13,24,26,27,31]. Chemotherapy has many adverse effects, among which oral symptoms and complications may be very severe [11,28].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of mucositis is up to 80% in BMT patients [14,16]. In a retrospective study, BMT patients with severe mucositis had an increased incidence of fever and infection and a fourfold increase in mortality [26]. Patients undergoing BMT have reported acute oral pain, mucositis and inability to eat as major sources of distress, and from the patient's perspective, oral mucositis is one of the most debilitating side effects of transplantation [2,9].…”
Section: Introductionmentioning
confidence: 99%